Teaching English with young learners: possibilities of critical language education (Via Litterae (ISSN 2176-6800): Revista de Linguística e Teoria Literária, 2020)
In the last two decades, we have observed an increase in research related to Teaching English to Young Learners (TEYL), and a consequent strengthening of the literature in this area, as pointed out by Tonelli and Pádua (2017). However, despite the achievements, there are still many challenges, such as the lack of regulation of the TEYL offer, the gap in teacher education and the instrumental view of teaching that language. Thus, based on memories of discussions held in a workshop conducted by the authors, the aim of this article is to defend the teaching English with children, reflecting on the possibilities of critical language education, revisiting understandings of what language means, as well as what teaching and learning languages in childhood means. To do so, we were guided by some authors (DUBOC; FERRAZ, 2018; JORDÃO, 2018; MONTE MÓR, 2019; LOPEZ-GOPAR, 2019; among others) to discuss our perspective of critical language education with children, presenting some activities that are part of our contexts and praxis. We hope that this work will encourage discussions about language education in foreign languages in childhood, aiming at valuing the context and reality of students and teachers, as well as the need to rethink the teacher education of those who work with TEYL.